Impact of circulating lymphoma cells at diagnosis on outcomes in patients with newly diagnosed de novo diffuse large B-cell lymphoma - Sayan Mullick Chowdhury; Subodh Bhatta; Timothy J. Voorhees; Kaitlin Annunzio; David A. Bond; Yazeed Sawalha; Audrey Sigmund; Walter Hanel; Lalit Sehgal; Lapo Alinari; Robert Baiocchi; Kami Maddocks; et al. (Journal of Hematology & Oncology)
Abstract Diffuse large B-cell lymphoma (DLBCL), the most common B-cell non-Hodgkin lymphoma rarely presents with circulating lymphoma cells (CL) at diagnosis. Previous studies were limited by small sample size precluding robust analysis. Hence, we evaluated the prognostic relevance of CL cells in newly diagnosed DLBCL patients. Based on peripheral blood (PB) immunophenotyping, patients were grouped into CL + and CL−. CL was defined as detectable clonally restricted B-cells that matched the actual or expected B-cell immunophenotype of DLBCL. The primary endpoint was progression-free survival (PFS), and secondary endpoints included overall survival (OS) and diagnosis-to-treatment interval (DTI). Among the 1266 patients with DLBCL, 621 had PB flow at diagnosis, and after excluding patients not meeting eligibility criteria, 588 cases remained. Among these, 85 (15%) were CL + and 503 were CL- (85%). Patients in CL + group were younger (67 vs. 70 years, p = 0.03) with a higher proportion of non-bulky disease (85% vs. 56%, p < 0.0001), normal albumin (79% vs. 54%, p < 0.0001), and MYC/BCL2 and/or BCL6 rearrangements (18% vs. 7%, p = 0.003) compared to the CL − group. Patients with CL at diagnosis had significantly inferior PFS and OS compared with those without CL. After adjusting for factors associated with inferior PFS and OS in univariable analysis, presence of CL remained significantly associated with inferior PFS (HR = 2.04, 95%CI = 1.47–2.84, p < 0.0001) and OS (HR = 1.61, 95%CI = 1.1–2.36, p = 0.01), respectively. There was no significant difference in DTI between the two groups. Given the prognostic relevance associated with presence of CL, clinicians should consider checking PB flow at diagnosis in all newly diagnosed DLBCL patients.